Associations between sweet taste function, oral complex carbohydrate sensitivity, liking and consumption of ad libitum sweet and non-sweet carbohydrate milkshakes among female adults. Issue 7 (14th October 2019) - Low, Julia Y. Q.; Lacy, Kathleen E.; McBride, Robert L.; Keast, Russell S. J.
Abstract: Excess energy intake is recognised as a strong contributing factor to the global rise of being overweight and obese. The aim of this paper was to investigate if oral sensitivity to complex carbohydrate relates to ad libitum consumption of complex carbohydrate foods in a sample group of female adults. Participants' (( n 51 females): age 23·0 (sd 0·6) years (range 20·0–41·0 years); excluding restrained eaters) sensitivity towards maltodextrin (oral complex carbohydrate) and glucose (sweet taste) was assessed by measuring detection threshold (DT) and suprathreshold intensity perception (ST). A crossover design was used to assess consumption of two different iso-energetic preload milkshakes and ad libitum milkshakes – (1) glucose-based milkshake, (2) maltodextrin-based milkshake. Ad libitum intake (primary outcome) and eating rate, liking, hunger, fullness and prospective consumption ratings were measured. Participants who were more sensitive towards complex carbohydrate (maltodextrin DT) consumed significantly more maltodextrin-based milkshake in comparison with less-sensitive participants ( P = 0·01) and this was independent of liking. Participants who had higher liking for glucose-based milkshake consumed significantly more glucose-based milkshake in comparison with participants with lower hedonic ratings ( P = 0·049). The results provide support regarding the role of the oral system sensitivity (potentially taste) to complex carbohydrate and the prospective to overconsume complex carbohydrate-based milkshake in a single sitting.